Genome-wide association study of agronomic traits in rice cultivated in temperate regions - Reig-Valiente, Juan L.; Marqués, Luis; Talón, Manuel; Domingo, Concha (Springer Nature, 2019)
Background: Rice plants are sensitive to the agro-climate conditions, being photoperiod one of main factor contributing to their adaptation to the region where they are grown. Dissecting the genetic bases underlying diversity in rice populations adapted to specific environmental conditions is a fundamental resource for breeding. In this study we have analysed a collection of japonica varieties adapted to temperate regions to perform association studies with traits of high agronomical interest such as heading date, plant height, number of panicles, panicle length and number of grains per panicle. Results: We have performed a genome wide association study using a panel of 1713 SNPs that, based on previous linkage disequilibrium estimations, provides a full coverage of the whole genome. We have found a total of 43 SNPs associated with variations in the different traits. The identified SNPs were distributed across the genome except in chromosome 12, where no associated SNPs were found. The inspection of the vicinity of these markers also revealed a set of genes associated with physiological functions strongly linked to agronomic traits. Of special relevance are two genes involved in gibberellin homeostasis that are associated with plant height and panicle length. We also detected novel associated sites with heading date, panicle length and number of grain per panicle. Conclusion: We have identified loci associated with important agronomic traits among cultivars adapted to temperate conditions. Some of these markers co-localized with already known genes or QTLs, but the association also provided novel molecular markers that can be of help to elucidate the complicated genetic mechanism controlling important agronomic traits, as flowering regulation in the non-dependent photoperiod pathway. The detected associated markers may provide important tools for the genetic improvement of rice cultivars in temperate regions.